Quantifying animal social behaviour with ecological field methods - Molly A. Clark; Christos C. Ioannou (Royal Society Open Science)
Field studies of social behaviour are challenging due to the need to record or infer interactions between multiple individuals, often under suboptimal environmental conditions or with potential disturbance by observers. Due to the limited field techniques available, we present a novel method to quantify social behaviours in the field by comparing the counts of individuals caught in traps across multiple locations sampled simultaneously. The distribution of individuals between traps gives the extent of aggregation, and phenotypic data allow for inference of non-random assortment. As a case study, we applied this method to populations of three-spined sticklebacks (Gasterosteus aculeatus) in freshwater ponds, using minnow traps. As expected, we observed a strong trend for aggregation. We were able to describe the ecological drivers of aggregation, comparing environmental and phenotypic conditions across sites. Aggregation was not related to environmental parameters, but was negatively associated with the proportion of breeding males caught during the breeding season. No evidence for phenotypic assortment based on body size was found. These results demonstrate that widely available ecological equipment can address questions related to social behaviour. This cost-effective approach, avoiding the tagging of individuals and minimizing extended observer disturbance, can be applied across various habitats and species.